Zoopoética ramalhiana: dramaturgia e imaginário animal em “O Pássaro Real”, “A Cabra Cabriola” e “Dom Ratinho e Dom Gatão" - Carvalho, Arthur Velázquez Florentino de (2025)
Pivoted by the itinerary of Maria de Lourdes Nunes Ramalho's children's and youth dramaturgy, this research aims to explore some poetics and imaginaries stemmed from animal creatures that foment the forms of characters and constitutions of personalities in three plays from her anthology Teatro Infantil: a collection of children's and youth texts, namely, “O Pássaro Real”, “A Cabra Cabriola”, and “Dom Ratinho e Dom Gatão”, with the goal of discussing which symbolic and cultural elements are present in the definition of Ramalho's zoopoetics. Understanding these plays as an aesthetic result of the playwright's compositional work, it was sought to investigate the formal relations engendered therein between the conventions of the vicentino auto, the entremés, and the brazilian northeastern pamphlet, marked by the structure strongly marked by what Propp (2012) denominates Folktale. Thus, through the lens of the aesthetic and symbolic representations of this zoo, it is intend to develop an analysis-interpretation of anthropological traits of the imaginary (Durand, 2012) that cross “simple forms” (Jolles, 1976) and rest on the corporality of typical characters, aesthetically formalized in a universe of allegorical representation, in this corpus, aimed at a preferential audience of children and young people. Through these allegories, this work probes the human ethos, facing certain approximations from biological (Quesado, 2009) or psychological (Chatelard; Ceiqueira, 2015) animality, reaching the nature of their instincts (Derrida, 2002) or their existential behaviors (Haraway, 2022). Finally, it is evident how all these poetic contingencies, allegories or imaginaries are involved in archetypal (Meletínski, 2019) and ethical (Berger, 2021) representations of femininities, (maternal and contrary to this paradigm) and aspects related to the rural (and/or urbanized) experience, marked by the exploitation and scarce resources of the poorest in tension with the power of the richest, as they subsist in the plot and in the creatures contained in the texts and in the Ramalhian characters involved in this zoopoetics.